An "all 5 mm ports" technique for laparoscopic day-case anti-reflux surgery: A consecutive case series of 205 patients. (November 2016) - Almond, L.M.; Charalampakis, V.; Mistry, P.; Hodson, J.; Lafaurie, G.; Matthews, J.; Singhal, R.; Super, P.
Abstract: Introduction: Laparoscopic anti-reflux surgery is conventionally performed using two 10/12 mm ports. While laparoscopic procedures reduce post-operative pain, the use of larger ports invariably increases discomfort and affects cosmesis. We describe a new all 5 mm ports technique for laparoscopic anti-reflux surgery and present a review of our initial experience with this approach. Methods: All patients undergoing laparoscopic fundoplication over a 35 month period from February 2013 under the care of a single surgeon were included. A Lind laparoscopic fundoplication was performed using an all 5 mm port technique. Data was recorded prospectively on patient demographics, operating surgeon, surgical time, date of discharge, readmissions, complications, need for re-intervention, and reasons for admission. Results: Two hundred and five consecutive patients underwent laparoscopic fundoplication over the study period. The all 5 mm port technique was used in all cases, with conversion to a 12 mm port only once (0.49%). Median operating time was 52 min 185 (90.2%) patients were discharged as day cases. Increasing ASA grade and the presence of a hiatus hernia were associated with the need for overnight stay with admission required in 33% of patients with ASA 3, compared to 4% with ASA 1 (p = 0.001), and 29% of those with a hiatus hernia vs. 5% without (p < 0.001). No port-related complications occurred, and no patients developed recurrence of reflux symptoms. A single patient required mesh repair of a large hiatus hernia. Conclusion: The all 5 mm ports approach to laparoscopic anti-reflux surgery is a safe, efficient, and cost-effective technique which facilitates same day discharge and minimises port related complications. National commissioning guidelines in the UK should target quality improvements in anti-reflux surgery based around day-case management. This would improve the service for these patients and culminate in cost savings for the NHS. Highlights: Two hundred and five patients underwent laparoscopic fundoplication using an all 5 mm port technique with conversion to a 12 mm port only once. In this unselected cohort, same day discharge was achieved in 89% of patients. Hiatal hernia repair using mesh was performed without the need to convert to larger ports.